Marx, Spinoza and the New Technologies - Finelli, Roberto (International Gramsci Journal, 2023)
The purpose of this essay is to investigate the nature of the ideology that is developing from new information technologies. The basic thesis is that there is a confusion between the accumulation and mathematical processing of “information” on the one hand and “knowledge” on the other. While knowledge, it is argued, is always based on the world of life, as a set of problems that arise from the materialistic, biological, emotional reproduction of a living human body, information represents the most abstract and formal version of it, which can be accumulated and calculated, but whose true meaning always depends on the meaning and reproductive intention of an organic-human life. Those who think of information as knowledge without a foundation in a materialistic and non-linguistic sense, fall into the ideology of conceiving the world as a massive information process and, consequently, of conceiving the human mind as a calculating machinic structure similar to the way a computer works. In this perspective, the essay, taking up the fundamental intuitions expressed by Gramsci in Americanism and Fordism, analyzes the origin of the term “Technology” in Marx's Capital, its distinction of meaning from the term “Technique” and the likely influence exercised in this field on the Marx’s thought from German Technologie, as a fundamental teaching discipline of the 18th century German Cameralism.